Therapeutic Approaches for Metastases from Colorectal Cancer and Pancreatic Ductal Carcinoma - Adriana G. Quiroz-Reyes; Jose F. Islas; Paulina Delgado-Gonzalez; Hector Franco-Villarreal; Elsa N. Garza-Treviño (MDPI AG, 2021)
Metastasis is the process of dissemination of a tumor, whereby cells from the primary site dislodge and find their way to other tissues where secondary tumors establish. Metastasis is the primary cause of death related to cancer. This process warrants changes in original tumoral cells and their microenvironment to establish a metastatic niche. Traditionally, cancer therapy has focused on metastasis prevention by systematic treatments or direct surgical re-sectioning. However, metastasis can still occur. More recently, new therapies direct their attention to targeting cancer stem cells. As they propose, these cells could be the orchestrators of the metastatic niche. In this review, we describe conventional and novel developments in cancer therapeutics for liver and lung metastasis. We further discuss the resistance mechanisms of targeted therapy, the advantages, and disadvantages of diverse treatment approaches, and future novel strategies to enhance cancer prognosis.